2002
DOI: 10.1080/13598660220135649
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Preservice Teachers' Dispositions Toward Critical Thinking: A cross-cultural perspective

Abstract: This study examined and compared the critical thinking dispositions (CT) of 218 American and 234 Chinese preservice physical education teachers. All were juniors or seniors and enrolled in physical education secondary teaching methods classes at the time of the study. Results provided evidence of a positive endorsement toward CT by the American sample, and a slight resistance by the Chinese participants on two of the four subscales from the California Critical Thinking Dispositions Inventory (CCTDI). The Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…In fact, however, when compared to students in New Zealand, the researchers found "no differences … between the groups on reported critical thinking use" (p. 121). Other studies by McBride et al (2002), Tiwari et al (2003) and Jones (2005) also found similar views on critical thinking between Western and Chinese students, with Westerners displaying comparable concerns about maintaining personal harmony with their peers. Finally, in interviews with Chinese students about their learning, Paton (2011) and O'Sullivan and Guo (2010) discovered that they had clear and positive ideas about critical thinking, displaying a strong sense of individuality and a rejection of conformism and rote learning.…”
mentioning
confidence: 62%
“…In fact, however, when compared to students in New Zealand, the researchers found "no differences … between the groups on reported critical thinking use" (p. 121). Other studies by McBride et al (2002), Tiwari et al (2003) and Jones (2005) also found similar views on critical thinking between Western and Chinese students, with Westerners displaying comparable concerns about maintaining personal harmony with their peers. Finally, in interviews with Chinese students about their learning, Paton (2011) and O'Sullivan and Guo (2010) discovered that they had clear and positive ideas about critical thinking, displaying a strong sense of individuality and a rejection of conformism and rote learning.…”
mentioning
confidence: 62%
“…The extant research reports that students in Asia are generally weak in critical thinking, especially when compared to their counterparts in the Anglophone countries (e.g. Atkinson, ; McBride et al ., ; Tiwari et al ., ; Turner, ). McBride et al .…”
Section: Introductionmentioning
confidence: 99%
“…This was the case with cooperative learning and play strategies, which, while used by teachers in China, were applied more often by teachers in Canada. Moreover, more than their Chinese counterparts, the Canadian teachers applied group discussion and formal teaching of prosocial behaviour as a method of promoting social integration, reflecting their cultural emphasis of critical thinking (McBride et al, 2002). Although there is a lack of research from both Canada and China on social integration, the methods used by the two countries are largely consistent with those considered effective for promoting social integration in the US (e.g., Brown et al, 2001;McCay & Keyes, 2001;Murray, 2002;Stockall & Gartin, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…For example, pre-service teachers in the US were found to endorse critical thinking skills whereas those in China did not (McBride, Xiang, Wittenburg, & Shen, 2002). Similarly, while US university students were more individualistic in their orientation toward learning, their Korean counterparts expressed more collectivist values in their beliefs about learning (Youn, 2000).…”
Section: Introductionmentioning
confidence: 89%